Fracture sonography – Literature review and current recommendations - Ackermann, Ole; Berthold, Daniel; Fischer, Christian; Grosser, Kay; Hauenstein, Christina; Kluge, Sebastian; Moritz, Jörg D; Tesch, Christian; v. Kaisenberg, Constantin (Ultraschall in der Medizin - European Journal of Ultrasound, 2024)
Purpose Over the course of more than two years, an expert group of 9 professional societies has created the S2e guidelines for fracture sonography. This publication summarizes the key points regarding the individual indications.Materials and Methods A systematic literature search was performed in PubMed, Google Scholar, and the Cochrane Database of Systematic Reviews from 2000 to March 2021 with evaluation of the literature lists. Randomized controlled clinical trials, observational clinical trials, meta-analyses, and systematic reviews were included. Guidelines, conferences, reviews, case reports, and expert opinions were excluded. Evidence was graded using the SIGN grading system 1999–2012, and the SIGN tables were then presented to the expert group. These were used to develop specific recommendations for the use of fracture sonography. All recommendations were discussed in detail and finally unanimously agreed upon.Results Of the 520 primary literature sources found, 182 sources (146 clinical studies and 36 meta-analyses and systematic reviews) were evaluated after screening and content assessment. 21 indications that allow reasonable application of fracture sonography were identified.Conclusion Ultrasound is a sensible, easy-to-use diagnostic method that is feasible for a large number of indications.
Keywords: Sonography; METHODS & TECHNIQUES; ultrasound; fracture; bone; diagnosis